The relationship between psychological abuse, athlete satisfaction, eating disorder and self-harm indicators in elite athletes - Willson, E.; Buono, S.; Kerr, G.; Stirling, A. (Frontiers in Sports and Active Living, 2025)
Introduction: Psychological abuse continues to be the most frequently reported type of maltreatment among athletes leading to negative mental health such as low mood and self-esteem, increased anxiety, self-harm, and eating disorders. Preliminary evidence suggests athlete satisfaction can influence the perceived outcomes associated with psychological abuse. Despite its negative impacts on athletes, psychological abuse continues to be justified as a tool to enhance athletic performance.